Retroperitoneal extraskeletal osteosarcoma with cystic change arising from heterotopic ossification: a rare entity - Agarwal, Kiran; Agarwal, Savita; Kumar, Lokesh (Annals of Pathology and Laboratory Medicine, 2015)
Extraskeletal osteosarcoma arising from myositis ossificans or heterotopic benign ossification is an extremely rare entity. Heterotopic ossification under rare circumstances may undergo malignant transformation and give rise to extraskeletal osteosarcoma however diagnosis of such transformation requires the presence of a remnant of the benign precursor lesion. Most of the cases reported as secondary extraskeletal osteosarcoma did not contain residual tissue of the previous benign condition and its presence was suggested solely on the basis of clinical course without any histopathological or radiological evidences. We describe a case of secondary extraskeletal osteosarcoma of retroperitoneum showing morphologic evidence of heterotopic benign ossification with extensive cystic change in an eighty- five year old female.